Term structure and cyclicity of value-at-risk: consequences for the solvency capital requirement - Frédérique Bec; Christian Gollier (Center for Economic Studies and ifo Institute (CESifo), 2009)
This paper explores empirically the link between French equities returns Value-at-Risk (VaR) and the state of financial markets cycle. The econometric analysis is based on a simple vector autoregression setup. Using quarterly data from 1970Q4 to 2008Q3, it turns out that the k-year VaR of French equities is strongly dependent on the cycle phase: the expected losses as measured by the VaR are twice smaller in recession times than expansion periods. These results strongly suggest that the European rules regarding the solvency capital requirements for insurance companies should adapt to the state of the financial market's cycle. To this end, we propose a cycle-dependent measure of the Solvency Capital Requirement.
Keywords: G11; 330; Expected equities returns; Value at Risk; investment horizon; vector auto-regression; Kapitalertrag; Value at Risk; Zinsstruktur; Konjunktur; Versicherung; Eigenkapitalvorschriften; Betriebliche Liquidität; Frankreich; Europa